Transición energética en España e integración de fuentes de energías no convencionales (2019)
This paper reviews the transition that the Spanish electricity market has had to include non-conventional energy sources. Although in Spain CO2 emissions between 2000 and 2018 have fallen by an average of 4.5 MtCO2/habitant, at the same time generation with non-conventional renewable energy sources, wind and solar, reached 25% of total generation in 2018. The costs of achieving these goals have been fully passed on to the end consumer, which has led, in part, to a tariff deficit in the Spanish electricity system. However, the implementation of Royal Decree Law 413/2014, which abolished the premium remuneration mechanisms for new generation projects with these sources, and implemented remuneration mechanisms via auctions to reward new investments with these technologies, has led to a stagnation in investments in these electricity generation sources.